The Thyroid cold nodule.: lts pathological significance - Delgado, Bolívar; Yametti, Luis; Cluzet, Oscar (Cirugía del Uruguay, 1984)
A series of 249 thyroid nodules were examined by gammagraphy, basically for determination of the histo• logical nature of cold nodules as well as their specificity and positive prediclive value in the thyroid cancer diagnosis.